2009
DOI: 10.1152/ajpregu.00354.2009
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training improves whole muscle and single myofiber size and function in older women

Abstract: Harber MP, Konopka AR, Douglass MD, Minchev K, Kaminsky LA, Trappe TA, Trappe S. Aerobic exercise training improves whole muscle and single myofiber size and function in older women. Am J Physiol Regul Integr Comp Physiol 297: R1452-R1459, 2009. First published August 19, 2009 doi:10.1152/ajpregu.00354.2009.-To comprehensively assess the influence of aerobic training on muscle size and function, we examined seven older women (71 Ϯ 2 yr) before and after 12 wk of cycle ergometer training. The training program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
206
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(231 citation statements)
references
References 57 publications
15
206
2
5
Order By: Relevance
“…While hypertrophic and strength gains have been reported following aerobic exercise in the elderly, the intensity used was relatively high for this cohort (60-80% of heart rate reserve) [86]. The benefit of aerobic exercise with BFR, is that both young [18,19] and elderly [20][21][22] populations can experience increases in muscle CSA and strength following walk or cycle training at much lower intensities, which is of particular benefit during the early progressions from surgery or illness [67].…”
Section: Elderly and Rehabilitation Participantsmentioning
confidence: 83%
“…While hypertrophic and strength gains have been reported following aerobic exercise in the elderly, the intensity used was relatively high for this cohort (60-80% of heart rate reserve) [86]. The benefit of aerobic exercise with BFR, is that both young [18,19] and elderly [20][21][22] populations can experience increases in muscle CSA and strength following walk or cycle training at much lower intensities, which is of particular benefit during the early progressions from surgery or illness [67].…”
Section: Elderly and Rehabilitation Participantsmentioning
confidence: 83%
“…A study by Harber et al (2010) showed that Forkhead transcription factor 3A (FOXO3A), which is an indicator of proteolytic systems, significantly decreased 6 h after an acute bout of 60 min cycle exercise compared to rest 45) . Furthermore, 12 weeks of cycle training, which induced muscle hypertrophy, significantly lowered the resting level of mRNA expression of FOXO3A 47,48) . Therefore, the attenuation of protein breakdown may be another factor contributing to muscle hypertrophy following a cycling training program.…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 96%
“…Therefore, it appears that a reduced expression following exercise results in muscle hypertrophy through a positive change in muscle net protein balance (90). Konopka et al (27,44) have shown that 12-week cycle training induced muscle hypertrophy and significantly reduced mRNA expression of Forkhead transcription factor 3A (FOXO3A) at rest with a trend for its downstream targets, Atrogin-1 and MuRF1, to also be reduced. Furthermore, FOXO3A significantly decreased 6 hours after an acute bout of 60-minute cycle exercise compared to rest (28).…”
Section: Proteolytic Gene Expressionmentioning
confidence: 99%
“…However, the vigorous training intensity and/or high training frequency might hinder some older adults from participating in this type of training program. Interestingly, recent studies have reported concurrent improvements in V O 2 max and muscle hypertrophy in young and older populations after single exercise training (27,62,64,65). These single exercise modes include ambulatory exercise (walking, jogging, and running), cycling, and swimming.…”
mentioning
confidence: 99%